Harmony Supply Chain: A New Construct towards Company Resilience - Sutarmin Sutarmin; Haryadi Haryadi; Novie Andri Setianto (International Journal of Supply Chain Management, 2020)
In the global business environment, the focus of competition shifts from companies against companies to supply chains against supply chains. A superior company must have an orientation to improve the company's resilience. Based on the literature review, there is no supply chain that clearly affects the company's resilience. Therefore, supply chain construction is needed that is able to develop the company's resilience. The harmony supply chain which is the result of hybridization between lean supply chains and responsive supply chains is expected to be a valid and reliable measurement tool in developing company resilience. A series of studies consisting of harmony supply chain testing as a valid and reliable measurement tool. The software used for testing is SPSS version 20 and AMOS version 18. The test results show that the harmony supply chain is a new construct as a valid and reliable measurement tool